Adverse Drug Reactions:A Retrospective Analysis from the ADR Monitoring Centre at a Tertiary Care Hospital - Fehmi Mushta Mukadam; Ujwala P. Gawali (Research Center for Rational Use of Drugs (RCRUD), 2024)
Background: Adverse Drug Reactions (ADRs) present significant challenges in healthcare, necessitating vigilant monitoring and analysis to enhance medication safety protocols. This retrospective study aimed to analyse ADRs reported at an Adverse Drug Reactions Monitoring Centre (AMC) to understand prevalence, patterns, and characteristics of ADRs. Methods: Retrospective data from January to December 2023 were collected from the AMC at Vaishampayan Memorial Medical College, Solapur. A total of 282 ADR reports were analysed for frequency, severity, implicated medications, patient demographics, and associated clinical factors. Causality assessment was performed using the WHO-UMC scale. Results: The majority of ADRs were associated with the oral route of drug administration (79.43%), and most were categorized as minor severity (68.44%) and probable causality (91.84%). Common ADR symptoms included vomiting (9.55%) and rash (9.22%). Antimicrobial agents were the most suspected drugs causing ADRs (17.38%). The study revealed discrepancies in ADR reporting patterns and highlighted the importance of pharmacovigilance in capturing and addressing ADR occurrences. Strategies to improve ADR reporting and enhance medication safety protocols are warranted to optimize patient care. Conclusion: Our study provides valuable insights into the prevalence, patterns, and characteristics of ADRs, emphasizing the need for continued surveillance and reporting to promote patient safety and improve healthcare outcomes.